Pengaruh Rotasi Tanaman Kacang Tanah (Arachis Hypogaea L.) Terhadap Kesuburan Tanah Dalam Mendukung Aktivitas Mikroba Tanah: Tinjauan Literatur - Della howu-howu Zendrato; Arni Lestari Waruwu; Priska Rahmat Yanti Zega; Yoel Melsaro Larosa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Crop rotation is an environmentally friendly agricultural method that is effective in maintaining soil fertility and reducing pest attacks. This study aims to assess the impact of legume crop rotation, especially groundnut (Arachis hypogaea L.), on soil quality. The study was conducted through literature studies from various scientific sources. Results show that groundnut is able to improve soil through symbiosis with nitrogen-fixing bacteria such as Rhizobium sp. and encourage functional microbial activities such as nitrifying bacteria (Nitrosomonas sp. and Nitrobacter sp.). Crop rotation also increases organic matter content, improves soil structure, and increases the availability of nitrogen in the form of nitrate that is easily absorbed by plants. In addition, root exudates from groundnuts enrich the rhizosphere with beneficial microorganisms. Overall, legume crop rotation contributes greatly to improving soil fertility in a natural and sustainable manner.